Biological activity of a standardized freeze-dried platelet derivative to be used as cell culture medium supplement. (May 2014) - Muraglia, Anita; Ottonello, Chiara; Spanò, Raffaele; Dozin, Beatrice; Strada, Paolo; Grandizio, Michele; Cancedda, Ranieri; Mastrogiacomo, Maddalena
Abstract Serum of animal origin and in particular fetal bovine serum is the most commonly utilized cell culture medium additive for in vitro cell growth and differentiation. However, several major concerns have been raised by the scientific community regarding the use of animal sera for human cell-based culture applications. Among the possible alternatives to the animal serum, platelet-derived compounds have been proposed since more than 10 years. Nevertheless, the high degree of variability between the different platelet preparations, and the lack of standardized manufacturing and quality control procedures, made difficult to reach a consensus on the applicability of this novel cell culture medium supplement. In this study, we describe the preparation of a standardized platelet-rich plasma (PRP) derivative obtained starting from human-certified buffy coat samples with a defined platelet concentration and following protocols including also freeze-drying, gamma irradiation and biological activity testing prior the product release as cell culture medium additive. Biological activity testing of the different preparations was done by determining the capability of the different PRP preparations to sustain human bone marrow mesenchymal stem cell (MSC) clone formation and proliferation. Taking advantage of a developed MSC in vitro clonogenicity test, we also determined biological activity and stability of the freeze-dried gamma-sterilized PRP preparations after their storage for different times and at different temperatures. The PRP effects on cell proliferation were determined both on primary cell cultures established from different tissues and on a cell line. Results were compared with those obtained in "traditional" parallel control cultures performed in the presence of bovine serum [10% fetal calf serum (FCS)]. Compared to FCS, the PRP addition to the culture medium increased the MSC colony number and average size. In primary cell cultures and in cell line cultures, the PRP promoted cell proliferation also in conditions where the FCS had not a proliferation stimulating effect due to either the nature of the cells and the tissue of origin (such as human articular chondrocytes from elderly patients) or to the critical low density cell seeding (such as for HeLa cells). In summary, the standardized PRP formulation would provide an "off-the-shelf" product to be used for the selection and expansion of several cell types also in critical cell culture conditions.